Tactical and strategical alternatives against anticipation defense to dangerous distance´s shooters - Anton Garcia, J. L. (EHF Web Periodical, 2014)
In this article I have tried to expose a few solutions against the problem mentioned at the beginning of the article. As we had said in the beginning, without doubt there will be other possibilities depending on the potential of the team and the individual player´s characteristics, as well as the used defensive system. Either one way or another, I want to point out as synthesis that all adopted solution must apply through the following general criteria: 1. Modifying space factors (occupied trajectories of the player, spaces, changes of spaces, places of penetration, exchanges, etc.). 2. Modifying temporary factors (moments of intervention, speed of execution, changes of rates, accelerations in the movements, etc.). 3. Modifying modal factors (to vary the executive models, tactical means used the type of action, arm´s position or the route to articulate the shooting, etc.).